Yield of kachri (Cucumis callosus) as influenced by organic and inorganic sources of nutrients in arid zone - JATAV, M K; SHARMA, B D; SAMADIA, D K; MEENA, S R (The Indian Journal of Agricultural Sciences, 2016)
The results showed that under hot arid agro-climate where soil is low in organic matter and available plant nutrients are of great importance in increasing yield by the balanced plant nutrients supply in Kachri (Cucumis callosus). It may concluded that combined application of 50% recommended dose of NPK (40 kg N+20 kg of P2O2 +20 K2O) along with 15 tonnes/ha FYM (in channel) gave higher yield (113.08 q/ha). Besides more yield, this treatment also showed increasing efficiency, net return and B: C ratio.